Sacral Neuromodulation for Neurogenic Lower Urinary Tract, Bowel and Sexual Dysfunction in Patients With Multiple Sclerosis: A Pilot Trial - Kobberø, Hanne; Krhut, Jan; Zvara, Peter; Pedersen, Torben Brøchner; Fode, Mikkel; Nielsen, Helle Hvilsted; Poulsen, Mads Hvid (Neurourology and urodynamics, 2025)
ABSTRACT Aims We present results of a two‐arm pilot study assessing the feasibility of conducting a double‐blind randomized controlled trial (RCT) to evaluate the efficacy of sacral neuromodulation (SNM) in patients with multiple sclerosis (MS) suffering from neurogenic lower urinary tract dysfunction (NLUTD). Methods Eligible subjects with refractory NLUTD and EDSS < 5 underwent SNM test phase. Those showing more than a 50% improvement of bladder variables, received implantable pulse generators (IPG) and were randomized to either treatment group (IPG ON) or to sham group (IPG OFF) for 1 month. During second month, all patients had the IPG ON until the end of the trial. The primary endpoints were trial feasibility, recruitment potential, and response rate at the end of SNM test phase. Secondary endpoint was safety. Changes in key bladder diary‐derived variables and patient reported outcomes were recorded as well. Results Thirty‐two patients were screened, 17 were eligible and 13 were included in the SNM test phase. Eleven were considered responders and were implanted with IPG. Subsequently, six patients were randomized to the treatment group and five to the sham group. No serious adverse events were reported. In the intervention phase, both objective and subjective improvements were seen in the treatment group, while the symptoms in the sham group remained mostly unchanged. At study completion, six patients reported being completely satisfied, three were mostly satisfied, and two were indifferent to the treatment. Conclusions This pilot trial demonstrated feasibility of double‐blind RCT assessing safety and efficacy of SNM in MS patients. Trial registration: ClinicalTrials.gov NCT05380856.